The biology and management of aerial populations of woolly apple aphid, Eriosoma lanigerum (Hausmann) (Homoptera: aphididae) - Heunis, J. M. (Juanita Maria) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2001.